2021
DOI: 10.3390/antiox10030348
|View full text |Cite
|
Sign up to set email alerts
|

Propolis in Metabolic Syndrome and Its Associated Chronic Diseases: A Narrative Review

Abstract: Propolis is a resinous product collected by bees from plants to protect and maintain the homeostasis of their hives. Propolis has been used therapeutically by humans for centuries. This review article attempts to analyze the potential use of propolis in metabolic syndrome (MetS) and its associated chronic diseases. MetS and its chronic diseases were shown to be involved in at least seven out of the top 10 causes of death in 2019. Patients with MetS are also at a heightened risk of severe morbidity and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 203 publications
0
20
0
1
Order By: Relevance
“…( 72 ) However, another investigation revealed that obese patients with NASH showed markedly higher expressions of these genes, suggesting that advanced stages of NAFLD might predispose to COVID‐19. ( 73 ) Gut microbiota and incomplete fatty acid oxidation products were also associated with NAFLD/NASH and severe COVID‐19, ( 74‐76 ) possibly by modulating host immune response. ( 77 )…”
Section: Fatty Liver and Covid‐19 Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 72 ) However, another investigation revealed that obese patients with NASH showed markedly higher expressions of these genes, suggesting that advanced stages of NAFLD might predispose to COVID‐19. ( 73 ) Gut microbiota and incomplete fatty acid oxidation products were also associated with NAFLD/NASH and severe COVID‐19, ( 74‐76 ) possibly by modulating host immune response. ( 77 )…”
Section: Fatty Liver and Covid‐19 Progressionmentioning
confidence: 99%
“…(72) However, another investigation revealed that obese patients with NASH showed markedly higher expressions of these genes, suggesting that advanced stages of NAFLD might predispose to COVID-19. (73) Gut microbiota and incomplete fatty acid oxidation products were also associated with NAFLD/NASH and severe COVID-19, (74)(75)(76) possibly by modulating host immune response. (77) Within the context of COVID-19, it has been clearly demonstrated that the presence of NAFLD/ NASH predisposes patients to severe COVID-19 morbidity and mortality.…”
Section: Fatty Liver and Covid-progressionmentioning
confidence: 99%
“…Several studies have shown that flavonoids, polyphenolic compounds present in propolis, possess anti-inflammatory capability [ 65 , 66 ]. The main reported mechanisms of anti-inflammatory activity of propolis include (i) inhibition of cyclooxygenase (COX) and subsequent inhibition of prostaglandin biosynthesis, (ii) free radical scavenging activity, (iii) inhibition of nitric oxide synthesis, (iv) reduction in inflammatory cytokine levels and (v) immunosuppressive activity [ 67 , 68 , 69 ].…”
Section: Propolis Bioactivitiesmentioning
confidence: 99%
“…Propolis extracts exhibit significant cellular recovery, as evidenced by the reversal of various biochemical indices and histopathology, altered due to CCl4 toxicity. Owing to the antioxidative potential, propolis has been assigned clinical importance and is useful for the treatment of metabolic syndrome and its associated chronic diseases [ 66 ]. Early on, using D-GalN-induced hepatic injury model, it was shown that ethanol extract of Brazilian and Cuban propolis types possess strong hepatoprotective activity against paracetamol- and CCl4-induced liver injury in mice and rat models [ 87 ].…”
Section: Propolis Bioactivitiesmentioning
confidence: 99%
See 1 more Smart Citation